(untitled) (De Musica, 2021)
This paper considers the issue of musical improvisational interactions in the digital era by pursuing the following three steps. 1) I will raise the question of the meaning and value of liveness, and in particular of live musical improvisation, in the age of the internet and discuss some effects of the so-called digital revolution on improvisation practices. 2) Then I will suggest that the interactions made possible by the web can be understood as kinds of live improvisational practices and I will briefly outline how such practices also involve musical improvisation. 3) Finally, I will focus on some aesthetic and philosophical aspects of new kinds of live improvisation made possible by recent progress in artificial intelligence research.